Cassandra Design Patterns - Sharma, Sanjay (Packt Publishing, 2014)
This is a step-by-step guide to understanding and using Cassandra in the real world. The book starts with the origins and capabilities of Cassandra and then allows the reader to journey through various real world use cases where Cassandra can be used successfully. The book also deep dives into how to use Cassandra for these use cases and applying the right design patterns.If you are an architect or developer wanting to design real world applications using Cassandra, this book is ideal for you. It would be helpful to have a background in Cassandra or programming concepts, but the book is readable for general users who have experience in any programming language or are aware of RDBMS solutions
Description based on publisher supplied metadata and other sources
Keywords: Apache (Computer file : Apache Group); Database management -- Computer programs